The role of diversity structure, dominance, and diameter of mangrove trees and mitigation of coastal abrasion at Darunu Village - Mandagi, Conny M.; Timpal, Tartius; Rompas, Vonny O.; Talimpong, Apriando; Gumolili, Youdi; Mait, Nicolaas H.; Lepar, Meita J. W. (Jurnal Ilmiah Platax, 2024)
Mangrove forests are vital for protecting coastal abrasion. This study investigates the diversity, dominance, and diameter distribution of Darunu Village mangroves and their potential to reduce coastal abrasion. Transect sampling was used and conducted at 2 stations with 3 observation sites. Three mangrove genera were found in Darunu Village, Rhizophora with 803 trees or 1.72%, Sonneratia with 95 individuals or 0.92%, and Avicennia with 33 individuals or 0.07%.  The Diversity Index (H') value at both stations was H’ = 0.27. or they were classified as a low category. According to those 3 mangrove genera at Darunu Village, the Rhizophora mangrove was dominant with a total of 1,881 individuals (D = 0,87). The diameter of all mangrove trees was ca. > 20 cm indicating potentially reduced wave energy. The suggestion needs to be special attention from the North Minahasa Government by providing mangrove cultivation and care for existing mangroves. The diversity of mangroves in Darunu Village was still low, can be overcome by planting other mangrove species that potentially the natural properties of mangroves in Darunu Village and other environmental factors. Field observations suggested the mangrove forest effectively mitigates coastal abrasion, This study underscores the importance of maintaining mangrove diversity for effective coastal protection. Keywords: Mangrove, Diversity, Dominance, Diameter Distribution,  Coastal Abrasion, Coastal Protection. Abstrak Hutan mangrove penting untuk perlindungan abrasi pantai. Penelitian ini meneliti keanekaragaman, dominasi, dan distribusi diameter mangrove di Desa Darunu, serta potensinya untuk mengurangi abrasi pantai. Transek sampling digunakan dan dilakukan di 2 stasiun dengan 3 lokasi observasi. Tiga genus mangrove ditemukan di Desa Darunu, yaitu Rhizophora sebanyak 803 pohon atau 1,72%, Sonneratia sebanyak 95 individu atau 0,92% dan Avicennia sebanyak 33 individu atau 0,07%.  Nilai Diversity Index (H') di kedua stasiun adalah H' = 0,27. atau diklasifikasikan sebagai kategori rendah. Menurut 3 genus mangrove di Desa Darunu tersebut,  mangrove Rhizophora mendominasi dengan jumlah 1.881 individu (D = 0,87). Diameter semua pohon mangrove sekitar > 20 cm terindikasi berpotensi mengurangi energi gelombang. Saran perlu mendapat perhatian khusus dari Pemerintah Minahasa Utara dengan menyediakan budidaya mangrove dan perawatan mangrove yang ada. Keanekaragaman mangrove di Desa Darunu masih rendah, dapat diatasi dengan penanaman spesies mangrove lain yang berpotensi menjadi sifat alami mangrove di Desa Darunu dan faktor lingkungan lainnya. Pengamatan lapangan menunjukkan bahwa hutan mangrove secara efektif mengurangi abrasi pantai, Studi ini menggarisbawahi pentingnya menjaga keanekaragaman mangrove untuk perlindungan pantai yang efektif. Kata kunci : Mangrove, Keanekaragaman, Dominance, Distribusi diameter,  Abrasi Pantai, Perlindungan pantai.